Opinions on the Inclusion of Men in Rhythmic Gymnastics: A Systematic Review (Revista Educación Física Chile, 2025)
Rhythmic Gymnastics (RG) has been traditionally associated with femininity due to its delicate and stylized movements, conditioned by gender norms. Despite restrictions from the International Gymnastics Federation (FIG), males have begun to venture into this discipline. This research analyzes the sports community's opinions regarding male incorporation in RG through systematic review using the PRISMA method. Scopus and Web of Science databases were consulted, collecting empirical articles published between 2014-2024. From 47 initial articles, 4 studies were selected according to specific criteria: personal opinions about male incorporation in RG and aspects related to participants' gender. Three types of opinions were identified among sports agents: favorable, unfavorable, and those that vary positively. Male participation faces unfavorable opinions due to gender stereotypes linked to the patriarchal system. However, close contact with male athletes can transform these positions toward more equitable perspectives.Unfavorable opinions predominate, affecting the continuity of male practice, although favorable ones, aligned with gender perspective and international regulations, promote inclusion.
Keywords: Sports Agents; Rhythmic Gymnastics; Gender Perspective; Opinions